Conditional Symmetry of a System of Nonlinear Reaction-Diffusion Equations - Barannyk, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
The conditional symmetry of a system of nonlinear reaction-diffusion equations is investigated. It is shown that the operators of conditional symmetry exist for the systems of nonlinear reaction-diffusion equations with an arbitrary number of independent variables. Moreover, these operators are found in the explicit form.